The Very Fairy Princess : Attitude of Gratitude - Andrews, Julie; Hamilton, Emma Walton; Davenier, Christine (New York ; Little, Brown and Company, 2016)
"Gerry, the very fairy princess, learns the importance of gratitude even in the face of disappointment over the course of Gratitude Day at school"--
Keywords: Gratitude -- Juvenile fiction; Schools -- Juvenile fiction; Princesses -- Juvenile fiction; Gratitude -- Fiction; Schools -- Fiction; Princesses -- Fiction; JUVENILE FICTION / Holidays & Celebrations / Thanksgiving; JUVENILE FICTION / Imagination & Play; JUVENILE FICTION / Royalty; JUVENILE FICTION / Social Issues / Self-Esteem & Self-Reliance; JUVENILE FICTION / Social Issues / Emotions & Feelings; JUVENILE FICTION / Girls & Women